2010
DOI: 10.1210/jc.2010-0482
|View full text |Cite
|
Sign up to set email alerts
|

An Antiinflammatory and Reactive Oxygen Species Suppressive Effects of an Extract of Polygonum Cuspidatum Containing Resveratrol

Abstract: The PCE-containing resveratrol has a comprehensive suppressive effect on oxidative and inflammatory stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 212 publications
(109 citation statements)
references
References 30 publications
4
102
0
Order By: Relevance
“…Crandall et al (49) examined in a small pilot study the effect of 4 weeks resveratrol treatment, with high doses of 1-2 g/ d on glucose homoeostasis in subjects with an impaired glucose tolerance, and reported that resveratrol was able to reduce postprandial glucose levels. These effects could not be confirmed by Ghanim et al (50) , who reported no beneficial effects of a 6-week intervention with an extract containing 40 mg resveratrol on HOMA-index, performed in healthy volunteers.…”
Section: Can Resveratrol Improve Metabolic Health?mentioning
confidence: 69%
“…Crandall et al (49) examined in a small pilot study the effect of 4 weeks resveratrol treatment, with high doses of 1-2 g/ d on glucose homoeostasis in subjects with an impaired glucose tolerance, and reported that resveratrol was able to reduce postprandial glucose levels. These effects could not be confirmed by Ghanim et al (50) , who reported no beneficial effects of a 6-week intervention with an extract containing 40 mg resveratrol on HOMA-index, performed in healthy volunteers.…”
Section: Can Resveratrol Improve Metabolic Health?mentioning
confidence: 69%
“…None of the reported changes were observed after the first 2 wk of resveratrol supplementation. It is also noteworthy that Ghanim et al [51] found that fasting glucose, insulin, or HOMA-IR scores remained unchanged following 6 wk of 40 mg resveratrol supplementation (in P. cuspidatum extract) in healthy individuals. Given that symptoms of hypoglycemia have not been reported in any of the bioavailability and safety studies, it appears that resveratrol is likely to be free from one of the major risks associated with many antidiabetic agents, making it an attractive choice if efficacy can be more thoroughly demonstrated.…”
Section: Obesity and Diabetesmentioning
confidence: 97%
“…This has been observed following red wine consumption [37,49,50], but has not yet been directly measured following resveratrol supplementation in humans. Ghanim et al [51] found that 6 wk of supplementation with 200 mg of P. cuspidatum extract containing 40 mg of resveratrol did not alter fasting plasma concentrations of cholesterol (total, LDL, and HDL), triglycerides, or leptin compared with placebo in 20 healthy individuals. However, mononuclear cells from the resveratrol group demonstrated suppressed nuclear factor kappa B (NFkB) binding, decreased ROS generation, and decreased tumor necrosis factor alpha (TNFa) and IL-6.…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
See 2 more Smart Citations